Determination of water sensitivity of nanosilica added hot mix asphalt - Geçkil, Tacettin; İnce, Ceren Beyza; Özpınar, Eda Tüzün (Fırat University, 2022)
In this study, the effects of nanosilica (NS) additive on the water sensitivity of hot mix asphalt (HMA) pavements were investigated. For this, NS-modified asphalts were prepared by adding NS at rates of 1%, 3%, 5% and 7% by weight to the pure B 160/220 asphalt. In the study, first of all, the physical properties of pure and modified asphalts were determined by penetration, ductility and softening point experiments, and their viscosities were determined by rotational viscometer (RV) experiment. Then, the optimum asphalt content of the mix was determined according to the Marshall design method. Hot mix asphalt specimens were prepared by keeping this determined ratio constant for pure and modified asphalts. Prepared pure and NS added modified mixture specimens were subjected to Marshall stability, retained Marshall stability (RMS) and indirect tensile strength (ITS) tests. The physical test results showed that the hardness and machinability temperatures of the modified binders increased up to 5% NS. According to the mixture test results, it was determined that NS additive had a positive effect on the sensitivity of road pavements to water, since Marshall stability, RMS and indirect tensile strength ratio (ITSR) values showed significant increases at 5% NS.
Keywords: Civil Engineering; İnşaat Mühendisliği